Name above all names - Begg, Alistair; Ferguson, Sinclair B. (Wheaton, Illinois : Crossway, 2013)
Jesus is the most important person in the life of the Christian. In this stimulating book, Begg and Ferguson explore the Bible's teaching on seven key attributes of Jesus's life and ministry, from Genesis to Revelation.
Cover; autors; copyright; Content; Preface; Jesus Christ, the Seed of the Woman; Jesus Christ, the True Prophet; Jesus Christ, the Great High Priest; Jesus Christ, the Conquering King; Jesus Christ, the Son of Man; Jesus Christ, the Suffering Servant; Jesus Christ, the Lamb on the Throne; backcover.
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Person and offices; Jesus Christ -- Divinity; Jesus Christ -- Knowableness; Jesus Christ -- Name